2023
DOI: 10.31989/bchd.v6i4.1067
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of Lactobacillus spp. and Rhodopseudomonas palustris probiotics

Abstract: Background: Probiotics have been used for many years to promote human health by mitigating  inflammation. However, its mechanics have not been fully elucidated. During inflammation, excessive and/or prolonged production of pro-inflammatory cytokines is related with various inflammatory diseases and cancer. Several probiotics have been reported as playing a role in suppressing the level of pro-inflammatory cytokines, as the human body attempts to recover. The aim of this study was to evaluate the anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Within the inflammation process, IL-6 and TNF-α cytokines emerge as primary pro-inflammatory mediators, predominantly generated by macrophages [16]. Polyphenols, such as phenolics and flavonoids have been reported to be able to suppress IL-6 and TNF-α cytokine levels and effectively inhibit LPS-induced NO Previous studies showed that these polyphenols had antiinflammatory activity on LPS-induced Raw264.7 macrophage models.…”
Section: Determination Of Bioactive Compounds (Phenolic Acidmentioning
confidence: 99%
“…Within the inflammation process, IL-6 and TNF-α cytokines emerge as primary pro-inflammatory mediators, predominantly generated by macrophages [16]. Polyphenols, such as phenolics and flavonoids have been reported to be able to suppress IL-6 and TNF-α cytokine levels and effectively inhibit LPS-induced NO Previous studies showed that these polyphenols had antiinflammatory activity on LPS-induced Raw264.7 macrophage models.…”
Section: Determination Of Bioactive Compounds (Phenolic Acidmentioning
confidence: 99%